Detection of oral human papillomavirus in HIV-positive men who have sex with men 3 years after baseline: a follow up cross-sectional study. - Jason J Ong; Tim R H Read; Lenka A Vodstrcil; Sandra Walker; Marcus Chen; Catriona S Bradshaw; Suzanne M Garland; Sepehr N Tabrizi; Alyssa Cornall; Andrew Grulich; Jane Hocking; Christopher K Fairley (PLoS ONE, 2014)
Human papillomavirus (HPV) is a causative agent in oropharyngeal squamous cell carcinoma. The natural history of oral HPV in HIV-positive men who have sex with men (MSM) is unclear.Detection of oral human papillomavirus in 173 HIV-positive MSM using oral rinse samples 3 years apart was investigated. HPV DNA was detected by polymerase chain reaction, and genotyped by Roche Linear Array.Of 173 men tested in 2010, 30 had at least one HPV genotype (17%, 95% CI: 12-23), 15 at least one hr-HPV (9%, 95% CI: 5-14) and 8 had HPV 16 (5%, 95% CI: 2-9) detected. In 2013, 33 had at least one HPV genotype (19%, 95% CI: 14-26), 20 had at least one hr-HPV (12%, 95% CI: 7-17) and 7 had HPV 16 (4%, 95% CI: 2-8) detected. Of 30 men at baseline (2010) with any HPV detected, 14 (47%, 95% CI: 28-66) had at least one persistent genotype. Of the 15 men in 2010 with high risk (hr-) HPV, 6 men (40%, 95% CI: 16-68) had at least one persistent hr-HPV genotype. The incidence rate of detection of at least one new HPV genotype was 4.8 per 100 person years (95% CI: 3.1-7.0), of at least one hr-HPV genotype was 3.2 per 100 person years (95% CI: 1.8-5.1) and of HPV 16 was 0.8 per 100 person years (95% CI: 0.2-2.0). The clearance rate was 14.9 per 100 person years (95% CI: 8.2-24.2) for any HPV, 18.2 per 100 person years (95% CI: 8.2-32.7) for hr-HPV and 17.4 per 100 person years (95% CI: 5.0-38.8) for HPV-16. Persistent HPV detection was associated with duration of HIV (OR 1.13 (per additional year), 95% CI: 1.00-1.26) and tonsillectomy (OR 8.17, 95% CI: 1.30-51.40).The same oral HPV genotype was detected again after 3 years in nearly half of HIV-positive men who have sex with men.